Meta-analysis for Supporting Empirical Theories in Educational Sciences - Sławomir Pasikowski (Nauki o Wychowaniu, 2025)
This article explores the role of meta-analysis and systematic review in developing and refining empirical theories in educational sciences. It highlights the method’s value in synthesizing research findings, identifying patterns, and improving the explanatory power and coherence of theories. It also underscores the skepticism present in academic circles, especially concerning meta-analysis. While meta-analysis is widely used in evidence-based approaches, its adoption in educational research sometimes remains locally limited due to concerns about data quality, methodological heterogeneity, publication bias, and perceived epistemic incompatibility with constructivist or interpretive paradigms. The author argues that these challenges can be addressed through methodological rigor, data transparency, proper contextualization, and interdisciplinary training in statistics, epistemology, and logic. Meta-analysis is presented not only as a statistical tool, but as a means of supporting intellectual inquiry and collaborative theory-building. The article calls for greater integration of meta-analytic methods into education research, emphasizing their potential to enhance the quality, comparability, and transparency of scientific knowledge.